Perceived stress linking psychosocial factors and depressive symptoms in low-income mothers - Mei-Wei Chang; Roger Brown; Duane T. Wegener (BMC, 2021)
Abstract Background Little is known about associations between perceived stress, psychosocial factors (social support, emotional coping, coping self-efficacy, and autonomous motivation), and depressive symptoms in low-income overweight or obese mothers of young children. Using baseline data of a lifestyle intervention study, this secondary analysis investigates whether perceived stress might mediate the associations between the psychosocial factors and depressive symptoms. Methods Convenience sampling was applied. Low-income overweight or obese mothers of young children were recruited from the Special Supplemental Nutrition Program for Women, Infants, and Children in Michigan, US. Survey data were collected through phone interviews. Participants (N = 740) responded to valid surveys measuring perceived stress, social support, emotional coping, coping self-efficacy, autonomous motivation, and depressive symptoms. Composite indicator structural equation modeling was performed to test for potential mediation. Results When investigating the potential role of perceived stress as a mediator, the indirect effects of social support (b = − 2.10, p < 0.01), emotion coping (b = − 3.81, p < 0.05), and coping self-efficacy (b = − 7.53, p < 0.01) on depressive symptoms through perceived stress were significant, but the indirect effect of autonomous motivation was not. Conclusion Future intervention studies aiming to alleviate depressive symptoms in low-income overweight or obese mothers of young children might consider including practical strategies to promote social support, emotional coping, and coping self-efficacy to reduce perceived stress, which might potentially decrease depressive symptoms. Trial registration Clinical Trials NCT01839708 ; registered February 28, 2013.